Emerging hepatitis B virus infection in vaccinated populations: a rising concern? - Tung-Hung Su; Pei-Jer Chen (Emerging Microbes and Infections, 2012)
Hepatitis B infection, especially by perinatal transmission, is endemic in Asian countries. After the first successful universal hepatitis B virus (HBV) vaccination programme for newborns in Taiwan, it became feasible to prevent HBV transmission and the resultant hepatocellular carcinoma in endemic countries. However, a small subset of vaccinated people have a suboptimal immunological response to vaccination, and the immunity of some young adults who were vaccinated as infants seems to have waned over time. Despite this loss, recent studies suggest that anamnestic anti-HBs antibody responses rapidly resume and eliminate acute HBV infection acquired through sexual contact or blood transfusion, even though the anti-HBs antibody titre has decreased below a protective level. These observations indicate prolonged protection by the HBV vaccine. Therefore, for people with a low infection risk, a universal booster vaccination is not currently recommended, but it should be considered for high-risk groups. However, we still advocate close monitoring of acute hepatitis B among patients who lack a protective level of anti-HBs antibody and suggest a wait-and-see policy to determine the necessity for booster vaccines.Emerging Microbes & Infections (2012) 1, e27; doi:10.1038/emi.2012.28